Criminal Imprisonment for Criminal Offenses Insults the President after State Court Decision Number: 013-022 / PUU-IV / 2006 (Study on State Court Blora Decision Number: 47 / PID. SUS / 2017 / PN.Blora) - Yustisi Yudhasmara; Umar Ma'ruf; Sri Endah Wahyuningsih (Jurnal Daulat Hukum, 2020)
The purpose of this study was to analyzing the impact of the juridical the removal of article criminal offense insult the president by the State Court Decision Number 013-022 / PUU-IV / 2006 as well as the consideration of Judges State Court of Blora in Decision No. 47 / Pid.Sus / 2017 / PN.Blora, as well as to analyze the existence of article insult the President in future be associated with the rise of social media.This study uses empirical juridical approach, the research specification descriptive. The data used in this study are primary data obtained from field studies that were analyzed qualitatively using the theory of criminal prosecution and criminal punishment, the theory of law enforcement and crime prevention theory. Then for secondary data obtained from ingredients documents or library materials.The final conclusion is that: The Impact of juridical when articles of insult against the President revoked, can damage the system in the inclusion of clauses concerning acts humiliation as a whole and also the revocation of article of insult against the President and Vice President do not have binding legal force so that their legal vacuum post the decision of the judge in the consideration while deciding the case No. 47 / Pid.Sus / 2017 / PN.Blora according to the indictment from the prosecutor. Because of Article 193 paragraph (1) of Act No. 8 of 1981 on Criminal Proceedings ( "Criminal Code") Existence of article insult the president in the future, should come up again all the rules, could reach the criminal insult the president with any form of media usedKeywords: Offense; insult the president; the State Court; RKUHP.